Current and Future Costs of Intractable Conflicts—Can They Create Attitude Change? - Rosler, Nimrod; Hameiri, Boaz; Bar-Tal, Daniel; Christophe, Dalia; Azaria-Tamir, Sigal (Frontiers in Psychology, 2021)
Members of societies involved in an intractable conflict usually consider costs that stem from the continuation of the conflict as unavoidable and even justify for their collective existence. This perception is well-anchored in widely shared conflict-supporting narratives that motivate them to avoid information that challenges their views about the conflict. However, since providing information about such major costs as a method for moderating conflict-related views has not been receiving much attention, in this research, we explore this venue. We examine what kind of costs, and under what conditions, exposure to major costs of a conflict affects openness to information and conciliatory attitudes among Israeli Jews in the context of the intractable Israeli–Palestinian conflict. Study 1 (N = 255) revealed that interventions based on messages providing information on mental health cost, economic cost, and cost of the conflict to Israeli democracy had (almost) no significant effect on perceptions of the participants of these prices, openness to new information about the conflict, or support for conciliatory policies. However, the existing perceptions that participants had about the cost of the conflict to Israeli democracy were positively associated with openness to alternative information about the conflict and support for conciliatory policies. Therefore, in Study 2 (N = 255), we tested whether providing information about future potential costs to the two fundamental characteristics of Israel, a democracy or a Jewish state, created by the continuation of the conflict, will induce attitude change regarding the conflict. The results indicate that information on the future cost to the democratic identity of Israel significantly affected the attitude of the participants regarding the conflict, while the effect was moderated by the level of religiosity. For secular participants, this manipulation created more openness to alternative information about the conflict and increased support for conciliatory policies, but for religious participants, it backfired. We discuss implications for the role of information about losses and the relationship between religiosity and attitudes regarding democracy and conflict.